ARE THE ELECTROMAGNETIC FIELDS A DANGER TO THE PUBLIC HEALTH? - Bularca Anca Roxana (Bulletin of University Transilvania of Brașov, 2020)
Electromagnetic fields of all frequencies represent one of the most common and fastest growing environmental influences, about which anxiety and speculation are spreading. All populations are now exposed to varying degrees of EMF and the levels will continue to increase as technology advances. As part of its activity to protect public health and in response to public concern, the World Health Organization (WHO) and other international organizations and scientists all over the world established increased politics and studies for analyzing the effects of EMF in the people’s lives. The International EMF Project in 1996 established, according to the scientific evidence of possible health effects of EMF in the frequency range from 0 to 300 GHz.